Nanoengineering-Enhanced Capillary Cooling Achieves Sustained Thermal Protection for Ultra-High Heat Flux and Temperature - Xu, Ruina (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.